2022
DOI: 10.3389/fmed.2022.844350
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Related Lesions in Newly Diagnosed Patients With Acute Leukemia: A Chinese Population-Based Real-World Study

Abstract: The relationship between newly diagnosed acute leukemia (AL) and heart-related lesions remains unclear. This study aimed to investigate baseline cardiac function and risk of cardiovascular diseases (CVDs) in patients with new-onset AL, and provide data on cardiac management strategies for patients with AL. We retrospectively collected data on baseline characteristics, echocardiography, and biochemical blood indicators (e.g., myocardial enzymes) from 408 patients, 200 with newly diagnosed AL, 103 with coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Xiao W et al found that newly diagnosed AL patients did experience some cardiac-related lesions prior to chemotherapy, and this injury persisted after adjusting for confounding factors. In addition, cardiac enzyme abnormalities were more severe in the hyperleukocytic leukemia subgroup (WBC count ≥ 100 × 10 9 /L), and the proportion of blasts was positively correlated with cardiac injury [ 20 ]. In agreement with our result, a retrospective study from Harvard Medical School also found that AL was associated with cardiac alterations before chemotherapy [ 27 ], which together with other similar studies [ 28 , 29 ], suggests that leukemia itself may cause direct damage to the heart prior to anti-tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao W et al found that newly diagnosed AL patients did experience some cardiac-related lesions prior to chemotherapy, and this injury persisted after adjusting for confounding factors. In addition, cardiac enzyme abnormalities were more severe in the hyperleukocytic leukemia subgroup (WBC count ≥ 100 × 10 9 /L), and the proportion of blasts was positively correlated with cardiac injury [ 20 ]. In agreement with our result, a retrospective study from Harvard Medical School also found that AL was associated with cardiac alterations before chemotherapy [ 27 ], which together with other similar studies [ 28 , 29 ], suggests that leukemia itself may cause direct damage to the heart prior to anti-tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is postulated that leukemia per se induces some cardiac injury through the release of excessive cytokines or infiltration of leukemic cells, even before the administration of anti-tumor medications. Our team conducted a cardiac assessment of newly diagnosed AL patients in the Chinese population and found that the myocardial enzyme levels in AL patients were significantly higher than those in healthy controls [ 20 ]. Consequently, we intend to investigate additional hematological risk factors linked to cardiac injury in newly diagnosed AML patients, with the ultimate goal of constructing a prediction model that would assist hematologists in identifying varying levels of risk and offering precise treatment options for individual patients.…”
Section: Introductionmentioning
confidence: 99%